Endovascular treatment of iliac artery rupture after septic embolization - Gazzani, Silvia Eleonora; Bianchini Massoni, Claudio; Marcato, Carla; Paladini, Ilaria; Rossi, Cristina (Acta Biomedica Atenei Parmensis, 2019)
A 56-year man with multiple comorbidities and recent septic embolization presented claudication intermittens (Rutherford3) at right lower limb and complaint in right lower quadrant at abdominal palpation. Duplex and computed tomography angiogram (CTA) showed a 64mm-pseudo-aneurysm (PA) originating from right common iliac artery, occlusion of external iliac and patency of hypogastric artery. An urgent endovascular approach was preferred. By left brachial percutaneous access, coil embolization (Balt SPI™ and Cook MReye™) of hypogastric and common iliac artery and deployment of Amplatzer Vascular PlugII™ into the common iliac artery were performed. Completion angiography showed exclusion of PA. One-day, 3‑day and 1-month CTA proofed no vascularization of PA. No fever, no leukocytosis, no signs of infection occurred during follow-up and 10-month CTA showed the complete resolution of pseudoaneurysm.